4-Hydroxy-3-methyl-2(1H)-quinolone, originally discovered from a Brassicaceae plant, produced by a soil bacterium of the genus Burkholderia sp.: determination of a preferred tautomer and antioxidant activity - Li, Dandan; Oku, Naoya; Shinozaki, Yukiko; Kurokawa, Yoichi; Igarashi, Yasuhiro (Beilstein Journal of Organic Chemistry, 2020)
4-Hydroxy-3-methyl-2(1H)-quinolone (1), a molecule known for a long time and recently discovered from a Brassicaceae plant Isatis tinctoria without providing sufficient evidence to support the structure, was isolated from a fermentation extract of Burkholderia sp. 3Y-MMP isolated from a soil by a Zn2+ enrichment culture. Detailed spectroscopic analyses by MS and NMR, combined with 13C chemical shift comparison with literature values of the related compounds and a synthetic preparation of 1, allowed its first full NMR characterization and identification of 2-quinolone but not 2-quinolinol (2) as the preferred tautomer for this heterocyclic system. While the metal-chelating activity was negligible, compound 1 at 10 μM, a concentration lower than that in liquid production cultures, quenched hydroxy radical-induced chemiluminescence emitted by luminol by 86%. Because some Burkholderia species are pathogenic to plants and animals, the above result suggests that 1 is a potential antioxidant to counteract reactive oxygen species-based immune response in the host organisms.
Keywords: antioxidant; Burkholderia sp; quinolone; soil bacterium; Zn2+ enrichment culture